When Symbolic Action Fails: Illustrations from Small-Claims Court - Yarbrough, Michael W. (Qualitative Sociology Review, 2013)
This article extends the cultural-pragmatics model of symbolic action developed by Jeffrey Alexander and his associates, which observes that symbolic action has become difficult in contemporary, highly differentiated societies. When symbolic action succeeds, the cultural-pragmatics approach argues it does so by re-“fusing” the elements of social performance, which have been disaggregated by the effects of social differentiation. Fusion produces affectively charged shared interpretations with the power to reshape the social world in important ways. Drawing on an example from my own ethnographic research, I argue that the current articulation of cultural pragmatics is unable to apprehend instances when such affectively charged shared interpretations are produced even when the actor or actors in a performance fail to achieve their performative goals. In this article I introduce the concept of “meta-performance” as a tool for analyzing such instances, arguing that this enables us to consider interpretive vantage points that are not conditioned by the actor’s intent. I then apply my extended meta-performative model to the ethnographic episode that inspired it. This bitterly fought court case between an adult daughter and her family produced a shared feeling among those assembled of hopeless deadlock between the family members, drawing a series of sharp symbolic boundaries – inter alia, between the daughter and her family and between “love” and “money” – not only despite, but precisely because all the participants’ component performances failed.